Determining the Adequacy of CFSR Data for Rainfall-Runoff Modeling Using SWAT. (2016) - Tomy, Tissa; Sumam, K.S.
Abstract: Stream discharge data are the essential information required to plan and design any watershed related project. In most of the cases, these data may not be available/ collected as there is no prior information regarding the commencement of a new project at the particular site. For a concerned watershed, number of stream gauge stations may be limited. But, due to the availability of large number of rain gauge stations, it is better to have rainfall – runoff model. However, land – based rain gauge stations do not always adequately represent the weather status of a watershed because they are point measurements, can be far from the characteristics of watershed of interest and can have gaps in their data series. Hence in the present study, the adequacy of CFSR (Climate Forecast System Reanalysis) data is determined to solve the problems of data deficiency in watersheds. Karuvannur watershed in Thrissur district is taken as the study area and is modeled using SWAT (Soil And Water Assessment Tool). Initially, the model was run for the available number of rain gauge stations. Then the model was executed by using CFSR data to find the accuracy of CFSR data in rainfall runoff modeling.